Randomized Phase III Trial of Adjuvant Pazopanib Versus Placebo After Nephrectomy in Patients With Localized or Locally Advanced Renal Cell Carcinoma - Motzer, Robert J; Haas, Naomi B; Donskov, Frede; Gross-Goupil, Marine; Varlamov, Sergei; Kopyltsov, Evgeny; Lee, Jae Lyun; Melichar, Bohuslav; Rini, Brian I; Choueiri, Toni K; Zemanova, Milada; Wood, Lori A; et al. (Journal of clinical oncology, 2017)
Purpose This phase III trial evaluated the efficacy and safety of pazopanib versus placebo in patients with locally advanced renal cell carcinoma (RCC) at high risk for relapse after nephrectomy. Patients and Methods A total of 1,538 patients with resected pT2 (high grade) or ≥ pT3, including N1, clear cell RCC were randomly assigned to pazopanib or placebo for 1 year; 403 patients received a starting dose of 800 mg or placebo. To address toxicity attrition, the 800-mg starting dose was lowered to 600 mg, and the primary end point analysis was changed to disease-free survival (DFS) for pazopanib 600 mg versus placebo (n = 1,135). Primary analysis was performed after 350 DFS events in the intent-to-treat (ITT) pazopanib 600 mg group (ITT600mg), and DFS follow-up analysis was performed 12 months later. Secondary end point analyses included DFS with ITT pazopanib 800 mg (ITT800mg) and safety. Results The primary analysis results of DFS ITT600mg favored pazopanib but did not show a significant improvement over placebo (hazard ratio [HR], 0.86; 95% CI, 0.70 to 1.06; P = .165). The secondary analysis of DFS in ITT800mg (n = 403) yielded an HR of 0.69 (95% CI, 0.51 to 0.94). Follow-up analysis in ITT600mg yielded an HR of 0.94 (95% CI, 0.77 to 1.14). Increased ALT and AST were common adverse events leading to treatment discontinuation in the pazopanib 600 mg (ALT, 16%; AST, 5%) and 800 mg (ALT, 18%; AST, 7%) groups. Conclusion The results of the primary DFS analysis of pazopanib 600 mg showed no benefit over placebo in the adjuvant setting.
Keywords: Male; Disease-Free Survival; lidé středního věku; Indazoles; senioři nad 80 let; Carcinoma, Renal Cell; Dose-Response Relationship, Drug; Pyrimidines; Aged, 80 and over; indazoly; sulfonamidy; vztah mezi dávkou a účinkem léčiva; Humans; pyrimidiny; Middle Aged; karcinom z renálních buněk; senioři; Kidney Neoplasms; mužské pohlaví; Female; Chemotherapy, Adjuvant; Aged; Sulfonamides; přežití bez známek nemoci; ženské pohlaví; Angiogenesis Inhibitors; mladý dospělý; Adult; Young Adult; Neoplasm Grading; Nephrectomy; stupeň nádoru; inhibitory angiogeneze; adjuvantní chemoterapie; dospělí; lidé; nefrektomie; Placebos; nádory ledvin; placebo